Kinetic frustration and the nature of the magnetic and paramagnetic states in iron pnictides and iron chalcogenides - Yin, Z. P.; Haule, K.; Kotliar, G. (Nature materials, 2011)
Iron-based superconductors all share the same building blocks. So why do local magnetic properties vary from one compound to another? A new theoretical model explains the variation in physical properties and links it to the structural differences, providing a description for a wide range of materials. The iron pnictide and chalcogenide compounds are a subject of intensive investigations owing to their surprisingly high temperature superconductivity 1 . They all share the same basic building blocks, but there is significant variation in their physical properties, such as magnetic ordered moments, effective masses, superconducting gaps and transition temperature ( T c ). Many theoretical techniques have been applied to individual compounds but no consistent description of the microscopic origin of these variations is available 2 . Here we carry out a comparative theoretical study of a large number of iron-based compounds in both their magnetic and paramagnetic states. Taking into account correlation effects and realistic band structures, we describe well the trends in all of the physical properties such as the ordered moments, effective masses and Fermi surfaces across all families of iron compounds, and find them to be in good agreement with experiments. We trace variation in physical properties to variations in the key structural parameters, rather than changes in the screening of the Coulomb interactions. Our results also provide a natural explanation of the strongly Fermi-surface-dependent superconducting gaps observed in experiments 3 .